2005
DOI: 10.1111/j.1469-8986.2005.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Airways, respiration, and respiratory sinus arrhythmia during picture viewing

Abstract: Emotional stimuli can cause airway constriction; however, it is uncertain whether a dimensional or categorical model of emotion can better describe airway changes. Also, little is known about the affective modulation of respiration and vagal activity, which can influence airway tone. We studied changes in oscillatory resistance (Ros), respiration, and respiratory sinus arrhythmia (RSA) in asthmatics and controls during viewing of affective pictures eliciting anxiety, depression, disgust, happiness, contentment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 66 publications
5
65
3
Order By: Relevance
“…This is in keeping with the lack of change in HR shown in humans when investigating physiological response to happiness induction with visual material such as pictures [36,37] or film clips [38]. Our results are also in agreement with [6] who found no average difference in HR for dogs when they were oriented towards their favourite toy.…”
Section: Accepted M Manuscriptsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in keeping with the lack of change in HR shown in humans when investigating physiological response to happiness induction with visual material such as pictures [36,37] or film clips [38]. Our results are also in agreement with [6] who found no average difference in HR for dogs when they were oriented towards their favourite toy.…”
Section: Accepted M Manuscriptsupporting
confidence: 81%
“…We were able to increase the duration of the recording from 5 s to 20 s using a novel stitching method. To our knowledge there are four studies that analysed short HRV intervals [27,47,48,49]. While Valenza et al [49] suggested an advanced computerized method to estimate emotions of less than 10 s, we on the other hand propose a non-computerized stitching method as a potential tool to investigate short-time HRV.…”
mentioning
confidence: 99%
“…Similarly, in the present study, RSA was not affected by the emotional value of the stimuli. Ritz and collaborators (Ritz et al, 2000(Ritz et al, , 2005Ritz and Thöns, 2002) suggested that RSA might be burdened with too much measurement error to provide a reliable index of vagal activity in instances of relatively mild stimulation, and that more intense emotional activation than that provided by picture stimulation could lead to clearer results. Even though highly arousing pleasant and unpleasant films were used in the present study, our results did not seem to highlight any effect of an intense stimulation on RSA 4 .…”
Section: Discussionmentioning
confidence: 97%
“…Another study, also using film clips, found no difference in cardiovascular reactivity between amusement and contentment . Happiness (which may or may not be the same as joy, as noted earlier) has been associated with greater increases in HR than surprise (Cacioppo et al, 1998), and smaller increases in respiratory sinus arrhythmia (RSA) than sexual desire (Ritz et al, 2005). Studies of the effects of positive emotional stimuli on respiration rate and respiratory amplitude have revealed both increases and decreases in both of these indices (for review see Boiten et al, 1994).…”
Section: Comparisons Of Autonomic Physiology Among Positive Emotionsmentioning
confidence: 96%